2020
DOI: 10.3390/medicina56010039
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Differences in Foreign Bodies Ingested by Children: A Cohort Study of 252 Japanese Cases

Abstract: Background and Objectives: When children accidentally ingest foreign bodies, they may be unable to communicate adequately; it is often difficult to identify the causative foreign body unless someone is watching over them. In such instances, to identify the causative foreign body during clinical practice, we aimed to determine if it varies according to age. Materials and Methods: From April 2013 to June 2018, 252 records of pediatric patients with a confirmed diagnosis of foreign-body ingestion were retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, the frequency of FBs in different categories vary between study populations, e.g. on second position sh bones were reported in Hong Kong [25], toys in the U.S. [7], plastics in Japan [31], and metallic objects in our study re ecting differences in the surrounding of children, the regional or cultural habits and agedependent preferences in the investigated populations. The ingestion pattern also differs by sex, age and season (e.g.…”
Section: Ingestion Of Foreign Bodies or Chemical Substances Is Frequementioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the frequency of FBs in different categories vary between study populations, e.g. on second position sh bones were reported in Hong Kong [25], toys in the U.S. [7], plastics in Japan [31], and metallic objects in our study re ecting differences in the surrounding of children, the regional or cultural habits and agedependent preferences in the investigated populations. The ingestion pattern also differs by sex, age and season (e.g.…”
Section: Ingestion Of Foreign Bodies or Chemical Substances Is Frequementioning
confidence: 59%
“…A retrospective observational study from Japan reported cigarettes be the most frequent FB (17%) in a cohort of younger children (median age 1 year 3 months) compared to only 2.3% registered cases in our study although the smoking prevalence in both countries are equivalent (WHO statistics data). In addition, the Yen coins are equivalent in size of 5 Cent to 2 Euro coins and should thus be as attractive for ingestion by toddlers [31]. Furthermore, the frequency of FBs in different categories vary between study populations, e.g.…”
Section: Ingestion Of Foreign Bodies or Chemical Substances Is Frequementioning
confidence: 99%
“…Fujisawa y cols. 13 , relacionaron la edad y el tipo de CE en niños japoneses, donde los cigarrillos y los plásticos fueron los más frecuentes entre lactantes con edad mediana de 12 y 11 meses respectivamente; y los objetos metálicos y monedas se recuperaron en niños mayores entre 35 y 42 meses, con una diferencia significativa según la edad p <0,01. El protocolo de atención de los pacientes, historia clínica, laboratorio básico y radiología estuvo ajustado según las guías 2,8 .…”
Section: Discussionunclassified
“…Consideramos que algunos casos presentan un síntoma inicial como tos o ahogo que desaparece en el tiempo, se suma la respuesta del cuidador y el entorno familiar que tiende a solapar el suceso. Fujisawa y cols 13 , encontraron que no hubo síntomas en el 60% de los pacientes, quizás por el tipo de CE, donde fue frecuente el cigarrillo. En el 40% restante de los pacientes, los síntomas dominantes fueron náuseas y vómitos, tos y alteración de la conciencia.…”
Section: Discussionunclassified
“…The absence of a witness presents challenges in pinpointing the causative foreign body, as young children may face difficulties in communication, and symptoms may not always be apparent. [3][4][5] The typical progression of foreign body (FB) ingestion suggests that 80-90% of foreign bodies will naturally pass through the gastrointestinal tract and be expelled; only 10-20% may require removal through endoscopic procedures, and less than 1% might necessitate surgical intervention. Diagnosis hinges on a heightened level of suspicion, often derived from parental reports of sudden-onset symptoms, observations https://doi.org/10.29309/TPMJ/2024.31.05.8006…”
Section: Introductionmentioning
confidence: 99%